Ethical imperatives of timely access to orphan drugs: is possible to reconcile economic incentives and patients’ health needs? - Rodriguez-Monguio, R. (Orphanet J Rare Dis, 2017)
BACKGROUND: More than 6,800 rare diseases and conditions have been identified in the US, which affect 25–30 million Americans. In 1983, the US Congress enacted the Orphan Drug Act (ODA) to encourage the development and marketing of drugs to treat rare diseases and conditions. This study analyzed all orphan designations and FDA approvals since 1983 through 2015, discussed the effectiveness of incentives for the development of treatments for rare diseases, and reflected on the ethical imperatives for timely access to orphan drugs. METHODS: Study data were derived from the Food and Drug Administration (FDA) Orange Book and the Office of Orphan Drugs Development. A search was conducted to assess literature on the ethical principles and economic incentives for the development of orphan drugs. RESULTS: In the period 1983–2015, the FDA granted 3,647 orphan drug designations and 554 orphan drug approvals. The orphan drug approvals corresponded to 438 different brand names. Cancer was the therapeutic area with the highest number of approvals. The increased number of patients with rare diseases and the growth in the cost of orphan drugs pose a significant economic burden for patients, public programs and private third party payers. Regulatory differences to qualify for orphan designation and various population thresholds employed by the FDA and the European Medicines Agency lead to further unmet health needs for patients with rare diseases and aggravate health inequities. There is no societal consensus on the population and economic thresholds, the drug effectiveness indicator(s), or the societal value to be placed for the approval and reimbursement of orphan drugs. CONCLUSION: Orphan drug development and marketing in the US concentrate in few therapeutic areas. Despite the increase in the number of FDA approved orphan drugs, the unmet needs of patients with rare diseases evidence that the current incentives are not efficiently stimulating orphan drug development. There is need to balance economic incentives to stimulate the development and marketing of orphan drugs without jeopardizing patients’ access to treatment. Thus, aligning pharmaceutical companies’ incentives with societal budgetary constraints is necessary and the ethical imperatives of timely access to orphan drugs need to be agreed upon.